Determining the authenticity of turmeric - N. L. Vostrikova; M. Yu. Minaev; K. G. Chikovani (Пищевые системы)
The paper examines the problem of the composition instability in the ready ground spice, turmeric. Analysis of the prevalent methods for turmeric adulteration and substances used for these purposes is given. The visual assessment of color tints of the turmeric root, spices containing it and chemical dyes based on chromium salts is presented. The studies on determination of the lead and chromium content were carried out to study the content of these metals and test the hypothesis of using lead chromate as a dye in adulteration of turmeric. Using the method of electrothermal atomic absorption spectroscopy, it was found that the lead content in the analyzed turmeric samples varied from 1.72 ± 0.58 to 5.03 ± 1.80 mg/kg, while the chromium content was in a range of 5.56 ± 0.85 to 16.15 ± 2.32 mg/kg. As a result of species specific PCR, wheat DNA was revealed in all purchased samples of ground turmeric. The levels of the main raw material replacement were established, which were 0.14% to 14.95% with the correlation coefficient close to 100%; efficiency of the reaction was 1.95, which was 97.5% when expressed as percentage. These levels of an undeclared allergen in the product composition can cause a serious allergic reaction. The authors tested the hypothesis of introduction of sodium and potassium salts for correction of the color spectrum in the ready spice and its correspondence to the natural color within the color spectrum of turmeric. As a result of the complex study of the spice composition, quite high values of chromium were found, presumably not only from the lead chromate compound but also from chromic acid salts, as the high level of potassium that significantly exceeded the native content of this element was found.